2020
DOI: 10.1097/sih.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Sim for Life: Foundations—A Simulation Educator Training Course to Improve Debriefing Quality in a Low Resource Setting

Abstract: Introduction Despite the importance of debriefing, little is known about the effectiveness of training programs designed to teach debriefing skills. In this study, we evaluated the effectiveness of a faculty development program for new simulation educators at Mbarara University of Science and Technology in Uganda, Africa. Methods Healthcare professionals were recruited to attend a 2-day simulation educator faculty development course (Sim for Life: Found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The ongoing pandemic limited the success of our recruitment, but this was a single condition study. As such, 18 participants is comparable or greater than similar studies ( Bench et al, 2019 ; Chang et al, 2019 ; Kattan et al, 2021 ; LeFlore et al, 2007 ; Michelet et al, 2019 ; Mormando et al, 2021 ; Robinson et al, 2020 ) and aligns with or exceeds minimal sample size recommendations ( Donner & Eliasziw, 1987 ; Jiin-Huarng & Wei-Ming, 2008). Based on a post-hoc power analyses comparing the population means of medical emotions in a previous study ( Duffy et al, 2020 ) to our study means, we had a sufficient sample size to achieve 80% power and 5% α values for all four medical emotion variables measured except for positive deactivating emotions.…”
Section: Methodssupporting
confidence: 64%
“…The ongoing pandemic limited the success of our recruitment, but this was a single condition study. As such, 18 participants is comparable or greater than similar studies ( Bench et al, 2019 ; Chang et al, 2019 ; Kattan et al, 2021 ; LeFlore et al, 2007 ; Michelet et al, 2019 ; Mormando et al, 2021 ; Robinson et al, 2020 ) and aligns with or exceeds minimal sample size recommendations ( Donner & Eliasziw, 1987 ; Jiin-Huarng & Wei-Ming, 2008). Based on a post-hoc power analyses comparing the population means of medical emotions in a previous study ( Duffy et al, 2020 ) to our study means, we had a sufficient sample size to achieve 80% power and 5% α values for all four medical emotion variables measured except for positive deactivating emotions.…”
Section: Methodssupporting
confidence: 64%
“…It is important that we take a focused look at whether the debriefing techniques that we learned are applicable to the environment in which we facilitate learning. [31][32][33] Debriefers should be encouraged to assess their learners beyond the usual age, sex, years of experience, and clinical profession by also considering their individual and group cultural compositions. Debriefers must also take care to avoid assumptions and generalizations that may not be true.…”
Section: Seek Cultural Education and Practicementioning
confidence: 99%
“…In our search for peer-reviewed articles in all languages with a focus on healthcare simulation debriefing and global cultural considerations during debriefing (not limited to particular study methods, profession, learner level, or date of publication), we found 3 articles (Table 2). [31][32][33] The purpose of these 3 articles differed greatly with a wide variation between methods, findings, and information reported, making it difficult to discuss recommendations for debriefers solely based on that data.…”
mentioning
confidence: 99%
“…These barriers can be addressed through targeted training in debriefing, support for less-experienced facilitators, including a video review to objectively establish the sequence of events and emphasize learning points, and interventions that focus on developing a culture of improvement [ 104 , 105 , 106 ]. For example, Sim for Life Foundations is a two-day course in debriefing developed for new faculty in simulation education in Uganda [ 110 ]. A pilot study of this curriculum demonstrated that faculty who completed the training showed a significant improvement in their debriefing skills that persisted at a 12-month reassessment.…”
Section: Post-event Reflection After Newborn Resuscitationmentioning
confidence: 99%